2008
DOI: 10.1182/blood.v112.11.516.516
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Secondary Prophylactic Versus On-Demand Sucrose-Formulated Recombinant Factor VIII Treatment in Adults with Severe Hemophilia A: Results from a 13-Month Crossover Study

Abstract: Many of the physical, psychosocial, and financial difficulties associated with severe hemophilia can be attributed to the effects of recurrent joint bleeds and chronic arthropathy. Regimens for clotting factor replacement treatment for hemophilia include prophylactic and on-demand therapy. A study in pediatric male patients with severe hemophilia A showed that prophylactic treatment with sucrose-formulated recombinant factor VIII (rFVIII-FS) resulted in prevention of joint damage and a decrease in the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
2
14
0
2
Order By: Relevance
“…Twenty‐nine prospective clinical studies reported from 1990 to 2010 with 3012 total patients at risk for de novo inhibitor development were included in the meta‐analysis [10,14–16,32–60]. All were published.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐nine prospective clinical studies reported from 1990 to 2010 with 3012 total patients at risk for de novo inhibitor development were included in the meta‐analysis [10,14–16,32–60]. All were published.…”
Section: Resultsmentioning
confidence: 99%
“…In response to inquiries, investigators of the included studies provided data not contained in the published study reports. Such supplementary data concerned study design [39,54], prior ED to FVIII [32,33,39,44], age [53], inhibitor testing frequency [39,44,49,53], patients with an inhibitor history [32,39,44,45,49], ED to rFVIII during study [15,16,44,49,51,53], peak inhibitor titer [55] and ED until inhibitor development [43–45,49,54,55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less clinical data are available in adults receiving secondary prophylaxis. One prospective study [42] of 19 evaluable patients has shown that patients with severe haemophilia A (FVIII < 1 IU dL )1 ) and a median age of 36 years, 80% of whom had target joints at study entry, treated with 25 IU kg )1 3 days a week, had a median of 0 bleeds in 6 months compared with a median of 21 bleeds while receiving on-demand treatment. The median (inter-quartile range) FVIII trough levels measured at 48 and 72 h in these patients were 6 (1-11) and 4 (0.5-6) IU dL )1 , respectively.…”
Section: Implications For Adults Compared To Childrenmentioning
confidence: 99%
“…Prophylaxis has been shown to prevent joint damage and significantly to reduce frequency of bleeds [4][5][6][7][8][9]. However, patients may still receive on-demand treatment for various reasons.…”
Section: Introductionmentioning
confidence: 99%